Cytoprotective drugs in cancer chemotherapy - Kozaczka, Anna; Kamińska-Budzińska, Grażyna; Machalski, Marek; Ścieszka, Maria (Contemporary Oncology/Współczesna Onkologia, 2001)
The basic problems of chemotherapy of neoplastic diseases still are harmful side effects on various organ cells. In this article we discuss the most commonly used cytoprotecive drugs diminishing toxic effects of popular cytostatics. The promising role seems to have: amifostine, dexrazoxane, mesna and silibinin.